Effect of Proteolytic Enzymes on Bacterial Flagella - Martinez, Rafael J. (1972)
Sheared flagella of Salmonella typhimurium strains SL 870 (Nml(+)Fla(+)) and SL 871 (Nml(−)Fla(+)) were found to be susceptible to proteolytic digestion by trypsin, chymotrypsin, and Pronase. The rate of tryptic digestion was similar for the ε-N-methyllysine-containing and the nonmethylated flagella. Thin fibers, which appeared to originate from only one end of the flagellar filament, were formed upon trypsin digestion. The fibers were not dissociated at extremes of pH or upon heating. The amino acid composition of the purified fibers was very different from that of intact Salmonella flagellin, and the fibers did not cross-react with antiflagellin or antiflagellar antiserum. The possible significance of these findings is discussed in relation to the flagellar structure.